Psychologiczne i prawne aspekty kontaktów osadzonych ojców z dziećmi - Jadach, Katarzyna; Sadowska, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The institution of parent–child contact is a parental right, characterized by a variety of forms of its implementation. It is to be, in addition to constitutional provisions, a normative guarantee for the protection of family ties and family life, regardless of the nature of the relationship between the child’s parents, their parental attributes, and their place of residence. One of the circumstances that can affect the quality of contacts in a special way is the fact that a parent is detained in prison. Therefore, the question arises as to the shape of the provisions of the executive criminal law and the actual activities undertaken in the penitentiary, aimed at protecting such family relations.
Keywords: kontakty z dzieckiem; osoba uwięziona; więzienie; więziony rodzic; ojciec